The Effect of Inquiry Learning Model on The Ability of Basic Passing Techniques In Futsal Games - Sahabuddin, Sahabuddin; Ishak, Muhammad (Sains Global Institut, Indonesia, 2024)
This study investigated the effect of the Inquiry Learning Model on the ability of basic passing techniques in futsal among students of State Senior High School 5 Makassar. Using a quasi-experimental design with a nonequivalent control group, two classes were purposively selected: the experimental group received instruction through the Inquiry Learning Model, while the control group was taught using conventional methods. Both groups consisted of 30 students. Data were collected through pretest and posttest skill tests assessing passing accuracy, strength, and speed. The normality and homogeneity tests confirmed data suitability for parametric analysis. The post-test results showed a significant improvement in the experimental group (mean = 85.3, SD = 4.7) compared to the control group (mean = 75.6, SD = 5.2), supported by the independent t-test (t(58) = 6.12, p < 0.001). The gain score analysis further demonstrated that the experimental group’s average gain (20.5 points) was significantly higher than that of the control group (10.3 points), indicating the effectiveness of the Inquiry Learning Model in enhancing futsal passing skills. These findings highlight the benefits of active, student-centred learning models in physical education to improve motor skill acquisition and performance. The study recommends integrating inquiry-based learning strategies in sports education to foster better technical competence and engagement. Further research is encouraged to examine the model’s impact on other sport-specific skills and broader student populations.